Estimation of the number of species using Poisson-Mixed model: a bayesian approach - Kumar, Sandeep; Kumar, Manoj; Pathak, Anurag; Mishra, Satya Prakash; Singh, Sanjay Kumar (Brazilian Journal of Biometrics, 2026)
This study presents an innovative method for estimating the number of species by using Poisson-Xgamma distribution. Classical and Bayesian estimation methods are applied to determine the number of species. The Jeffrey’s and Reference prior has been proposed for estimating the number of species under Bayesian framework. The proposed Bayes estimators via Jeffrey’s and reference prior have been compared through simulated risks (RMSE). The applicability of the proposed work have been validated through Mount Kenya’s insect species dataset.